An PENTINGNYA NEW JOB SKILLS DAN LIFE SKILLS BAGI ASN DALAM MENGHADAPI TANTANGAN DI ERA NEW NORMAL - Nanik Widyaningsih Widyaningsih (Jurnal Kewidyaiswaraan, 2020)
The Covid-19 pandemic has changed the work system of workers including state sipil servants (ASN) who previously worked in offices forced to adopt a work from home work (FWH) pattern. After the pancemic lasted several months, the effecitiveness of WFH was considered less effective as indicated by an increase in public complaints about public services. The new normal is a new government policy at work but has its own challlanges. Related to that, the problem in this paper in what are the challanges of ASN in the new normal era and what are the things must have in order to work effictively and efficiently? This study uses a literature study approach, which examines various writings, literature ralated to the pandemic and the new normal. The results of the study show that ASN working in the new normal period has heavier challanges in terms of several things, namely risk, workload, targets/achievements, and work methods. So that ASN can work effectively and efficiently in the new normal, it is necessary to have new job skills and life skills. The new jobs skills include: adaptability and flexibility skill, new forming good habits skill, tech Savviness, creative thinking and critical thinking, decision making and problem solving, effective communication and Interpersonal relationship, commit to a lifetime of learning. While in terms of life skills, ASN need to have self awareness, emphathy, assertiveness and equanimity/self control, resilience, ability cope with stress and emotions.